Host mitochondria: more than an organelle in SARS-CoV-2 infection - Shoraka, Shahrzad; Samarasinghe, Amali E.; Ghaemi, Amir; Mohebbi, Seyed Reza (Frontiers in Cellular and Infection Microbiology, 2023)
Since December 2019, the world has been facing a new viral pandemic called COVID-19 (Coronavirus disease 2019) caused by a new beta-coronavirus named severe acute respiratory syndrome coronavirus-2, or SARS-CoV-2. COVID-19 patients may present with a wide range of symptoms, from asymptomatic to requiring intensive care support. The severe form of COVID-19 is often marked by an altered immune response and cytokine storm. Advanced age, age-related and underlying diseases, including metabolic syndromes, appear to contribute to increased COVID-19 severity and mortality suggesting a role for mitochondria in disease pathogenesis. Furthermore, since the immune system is associated with mitochondria and its damage-related molecular patterns (mtDAMPs), the host mitochondrial system may play an important role during viral infections. Viruses have evolved to modulate the immune system and mitochondrial function for survival and proliferation, which in turn could lead to cellular stress and contribute to disease progression. In this regard, recent studies have focused on the possible roles of mitochondria in SARS-CoV-2 infection. It has been suggested that mitochondrial hijacking by SARS-CoV-2 could be a key factor in COVID-19 pathogenesis.In this review, we discuss the roles of mitochondria in viral infections including SARS-CoV-2 infection based on past and present knowledge. Paying attention to the role of mitochondria in SARS-CoV-2 infection will help to better understand the pathophysiology of COVID-19 and to achieve effective methods of prevention, diagnosis, and treatment.